The Association of Dry Eye Symptom Severity and Comorbid Insomnia in US Veterans. (September 2018) - Galor, Anat; Seiden, Benjamin E.; Park, Jasmine J.; Feuer, William J.; McClellan, Allison L.; Felix, Elizabeth R.; Levitt, Roy C.; Sarantopoulos, Constantine D.; Wallace, Douglas M.
Abstract : Purpose: To investigate the association between dry eye (DE) and insomnia symptom severity. Methods: Cross-sectional study of 187 individuals seen in the Miami Veterans Affairs eye clinic. An evaluation was performed consisting of questionnaires regarding insomnia (insomnia severity index [ISI]) and DE symptoms, including ocular pain, followed by a comprehensive ocular surface examination. Using a two-step cluster analysis based on intensity ratings of ocular pain, the patient population was divided into two groups (high and low ocular pain groups: HOP and LOP). A control group was ascertained at the same time from the same clinic as defined by no symptoms of DE (Dry Eye Questionnaire 5 [DEQ5], <6). The main outcome measure was the frequency of moderate or greater insomnia in the DE groups. Results: The mean age of the study sample was 63 years, and 93% were male. All insomnia complaints were rated higher in the HOP group compared with the LOP and control groups ( P <0.0005). Most (61%) individuals in the HOP group experienced insomnia of at least moderate severity (ISI≥15) compared with the LOP (41%) and control groups (18%) ( P <0.0005). Black race (odds ratio [OR], 2.7; 95% confidence interval [CI], 1.2–6.0; P =0.02), depression severity (OR, 1.2; 95% CI, 1.1–1.3; P <0.0005), and DE symptom severity (DEQ5; OR, 1.1; 95% CI, 1.01–1.2; P =0.03) were significantly associated with clinical insomnia (ISI≥15) after controlling for potential confounders. Conclusions: After adjusting for demographics and medical comorbidities, we show that DE symptom severity is positively associated with insomnia severity.